USE OF CASE STUDY TECHNOLOGY IN IMPROVING PRACTICAL COURSES IN NUCLEAR PHYSICS - K. R. Nasriddinov (International Journal of Innovations in Engineering Research and Technology, 2022)
This article is devoted to the use of case-study technology in improving practical training in nuclear physics, and the aspect of increasing efficiency using case-study technology in passing practical training in the department of nuclear physics is analyzed.